Papua New Guinea food price bulletin: July 2022 - International Food Policy Research Institute; Kedir Jemal, Mekamu; Schmidt, Emily (International Food Policy Research Institute, 2022)
This bulletin presents food price data compiled by the International Food Policy Research Institute (IFPRI) and Fresh Produce Development Agency (FPDA) from markets across the country to track food price trends and inform policymakers. In addition, users can access a web-based interactive dashboard for visualizing monthly prices of over 20 different food types over time. Price data collected in 2021 had comparatively higher number of observations compared to the previous year. However, data collection was interrupted in August through mid-September due to logistical challenges and market closures as a result of the COVID-19 surge in PNG, mainly in highland markets, creating gaps in the time series price data.